STRATEGY IN ANTICIPATING THE HOSPITAL’S FINANCIAL CONDITION DURING THE COVID-19 PANDEMIC: A SYSTEMATIC REVIEW - Jatnika, Viana Villamanda; Soewondo, Prastuti; Muliawati, Mutia (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
As of June 9, 2021, the number of confirmed COVID-19 patients was 174 million, and the death toll was 3.76 million. In the current pandemic situation, the function of hospitals as a place for treatment and health rehabilitation services meeting hospital service standards is very much needed. However, with the emergence of COVID-19 causing the financial stability of the hospital has been undermined. The purpose of this systematic review is to discuss strategies in predicting the financial status of hospitals in various countries to face the pandemic. Included study within periods 2020, type of research articles published in the field of public health and hospitals related to the COVID-19 pandemic National and international research articles relating to hospital financial strategies. The search, using a multi-method strategy and downloaded it into Mendeley. Strategies that can be taken include change of leadership style, social media strategy, funding allocation system, rejuvenating income, SWOT analysis, and health policy. The management approach to establishing a stable financial condition is to reduce unnecessary costs and improve planning and execution. These things must be evaluated immediately so that decisions can be taken immediately to prevent the financial deficit that will continue to occur.